Nasab Bayi Tabung dalam Perspektif Agama Islam; Tinjauan Hukum - Hasanuddin, Ahmad; Ansori, Miswan (Isti`dal : Jurnal Studi Hukum Islam, 2024)
In the era of globalization as it is today, technological advancements have indeed greatly aided many fields, especially in healthcare. One of them is the technology in the field of in vitro fertilization (IVF) programs, which is increasingly sophisticated and intended for couples who are infertile. IVF is one method to address fertility issues when other methods have failed. However, as it develops, issues have arisen where initially this program was widely accepted by all parties due to its noble purpose, but recently  it has become controversial. The purpose of this research is to determine the legal status of babies born through artificial insemination (IVF), and to understand the relationship of the baby with its biological parents and with the surrogate mother.